AL-QUR’AN SEBAGAI SUMBER PENDIDIKAN ISLAM - Rudi Ahmad Suryadi (Taklim : Jurnal Pendidikan Agama Islam, 2022)
AbstractThe Qur'an is the main reference source for understanding life's problems, including educational issues. The Qur'an as hudan and bayyinat, provided a positive impetus for its readers to understand more deeply the signs of God's unlimited power, one of which is the thought of education. The Qur'an is a normative source for deriving the theory of Islamic education as well as being the basis. The process of deriving ideas requires the principles of philosophical thought, science, and educational interpretation. The source of revelation, namely the Qur'an and hadith, occupies the top position as the source and foundation of Islamic education theory. Research on the source of revelation will derive the theory as the basis for the development of educational theory at the level of educational philosophy. The theory at the philosophical level is derived from the theory of educational science. Finally, the theory at the level of educational science is revealed in the educational manual as educational practice. This kind of research is oriented towards exposing the concept of education in the Qur'anic cues through various thoughts and outlining the idea of educational goals derived from the development of educational theory.Keywords: Al-Qur’an, Source of Islamic Education, Islamic Education AbstrakAl-Qur'an merupakan sumber rujukan utama untuk memahami masalah kehidupan, termasuk masalah pendidikan. Al-Qur'an sebagai hudan dan bayyinat, memberikan dorongan positif bagi para pembacanya untuk memahami lebih dalam lagi tanda-tanda kekuasaan Tuhan yang tidak terbatas, salah satunya pemikiran tentang pendidikan. Al-Qur'an merupakan sumber normatif untuk menurunkan teori Pendidikan Islam sekaligus menjadi landasannya. Proses pemunculan gagasan membutuhkan prinsip-prinsip pemikiran filosofis, ilmu pengetahuan, dan interpretasi pendidikan. Sumber wahyu, yaitu al-Qur’an dan hadits menempati posisi teratas sebagai sumber dan landasan teori Pendidikan Islam. Penelitian tentang sumber wahyu akan menurunkan teori sebagai landasan pengembangan teori pendidikan pada tataran filsafat pendidikan. Teori pada tataran filosofis diturunkan dari teori ilmu pendidikan. Terakhir, teori pada tataran ilmu pendidikan diungkap dalam buku pedoman pendidikan sebagai praktik pendidikan. Penelitian semacam ini diorientasikan untuk mengungkap konsep pendidikan dalam isyarat al-Qur'an melalui berbagai pemikiran dan menguraikan gagasan tujuan pendidikan yang diturunkan dari pengembangan teori pendidikan.Kata Kunci: Al-Qur’an, Sumber Pendidikan Islam, Pendidikan Islam